Morphological, physiological, and molecular studies on the effect of shoot architecture on phase change and floral transition in Eucalyptus occidentalis and Metrosideros excelsa : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology at Massey University, Palmerston North, New Zealand - Jaya, Elizabeth S.K.D. (Massey University, 2007)
Shoot morphogenesis in Eucalyptus occidentalis and Metrosideros excelsa was analysed at the morphological, physiological and molecular levels to understand the regulation of phase change and the floral transition. Study of the regulation of these developmental plant processes is limited in woody species due to their long juvenile phase. Six ecotypes of E. occidentalis were grown to two predetermined architectures (free branching or single stem). Free branching plants of ecotype 13648 displayed adult shoot phenology (lanceolate leaves) earlier than single stem counterparts. In addition, changes in leaf morphology in free branching plants were accompanied with changes in leaf anatomy and gas exchange signifying that in E. occidentalis complexity of shoot architecture had a significant effect on rate of phase change. Flowering was observed in all but one ecotype irrespective of architecture demonstrating that vegetative phase change and floral transition are temporally uncoupled in this species. To understand the floral transition at the molecular level in E. occidentalis, partial homologues of the inflorescence meristem identity gene TERMINAL FLOWER1 and floral meristem identity genes LEAFY and APETALA1 were isolated. The expression patterns of these meristem identity genes during development of free branching and single stem plants were analysed by quantitative real-time PCR. Increased levels of expression of EOLFY and EOAP 1 (relative to α -TUBULIN) were displayed at more proximal nodes in free branching plants than in single stem plants. Elevated floral meristem identity gene expression levels correlated with flower initiation. Further, effects of architecture and environment on gene expression were monitored in E. occidentalis. The overriding effect of shoot architecture on the floral transition was observed under warm long day and ambient environments. Elevated levels of EOLFY and EOAP 1 were correlated with floral bud score and EOAP1 was found to be a reliable marker of floral transition in E. occidentalis. Low levels of EOTFLI expression were detected in buds irrespective of their position on the plant leading to the suggestion that this might have contributed to the precocious flowering observed in this species. In contrast to E. occidentalis, M excelsa attained adult shoot phenology (pubescent leaves) faster when grown as single stem plants than as free branching plants. It appears that growth as height is required for vegetative phase change in this species. However, floral transition occurred only once single stem plants were allowed to branch. Vegetative phase change and the transition to flowering seem to be coordinated in this species with the former being a pre-requisite for the latter.
Keywords: Pohutukawa; Morphogenesis; Gene expression; Floral transition; Fields of Research::270000 Biological Sciences::270200 Genetics::270201 Gene expression